Association Between Gestational Weight Gain According to Three International Charts and Child Adverse Outcomes in Brazil: Results from Multiple Cohort Data (P11-126-19). (13th June 2019) - Carrilho, Thais; Farias, Dayana; Batalha, Monica; Alves, Ronaldo; Costa, Nathalia; Gonzalez, Mylena; Aguiar, Emanuelli; Kac, Gilberto; Consortium, Brazilian Gestational Weight Gain; Domingues, Marlos; Drehmer, Michele; Granado, Silvana; et al.
Abstract: Objectives: To evaluate the association between gestational weight gain (GWG) classified according to three international charts and adverse child outcomes in the Brazilian population. Methods: Data from 12 cohorts conducted in Brazil (1990-2018) were combined in a pooled dataset of 15, 066 women. Weight and gestational age were measured. Adult (18-48 years) women with singleton pregnancies and free of hypertension and diabetes were included. Selected centiles of three international charts were used [Life-cycle project – L charts, Intergrowth-21st - I chart and Hutcheon – H charts]. Total GWG was calculated as: difference between the weight measured up to 14 days before delivery and the weight measured in the 1st trimester (I chart) or the pre-pregnancy self-reported weight (L and H charts). The outcomes were small and large for gestational age infants (SGA/LGA,  < 10th/ > 90th - Intergrowth centile), low birth weight (LBW,  < 2500g) and macrosomia (> 4000g). Multinomial logistic regressions were fitted for selected centiles (lowest: 3rd, 5th, 10th, 25th; highest: 75th, 90th, 95th, 97th) to evaluate the charts' performance in the prediction of the outcomes. Results: A total of 7, 456 women were included in the analysis. Total GWG was 12.1 kg (SD = 5.9) and GWG from the 1 st trimester to delivery 10.9 kg (SD = 4.8). The prevalence of SGA was 6.6%, LGA, 14.9%, LBW, 6.5% and macrosomia, 4.7%. For all charts, women who gained weight in the lowest centiles presented higher prevalences of SGA and LBW in comparison to those on the highest centiles, while women with gains in the highest centiles, presented higher prevalences of LGA and macrosomia. L charts presented a better performance to predict outcomes, i.e., women with gains in the highest centiles were associated with increased odds of LGA and macrosomia and those in the lowest centiles with increased odds for SGA and LBW. Analysis based on H charts provided similar results. The poorest performance was observed for I charts, in which only women with gains on the higher centiles were associated with the occurrence of LGA (Figure ). Conclusions: L charts seem to better predict the occurrence of child outcomes. Further investigation is needed to decide the most appropriate chart and cutoffs for GWG recommendations for the Brazilian population, considering maternal and child adverse outcomes. Funding Sources: The Brazilian National Council for Scientific and Technological Development and Bill and Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: